Royal Estates and Public Prerogatives in Medieval Italy: An Interdisciplinary Approach (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The article outlines the main contents and objectives of the PRIN research project Fiscal Estate in Medieval Italy: Continuity and Change (Ninth-Twelfth Centuries) and provides an overview of the three workshops organised in the first semester of 2022. The first workshop revolved around the transformations of the fiscal patrimony from the Roman empire to the post-Roman kingdoms in western Europe (Rome, February 2022); the second workshop dealt with the connections between the patterns of change in the exploitation of the royal domain, on the one hand, and medieval economic growth on the other (Bologna, May 2022); the third one discussed water rights and inland waterways in medieval Italy between the eighth and the thirteenth centuries, and involved both archaeologists and historians (Turin, May-June 2022).
Keywords: Fiscal Estates; Middle Ages; Late Roman Empire; Economy; Rivers